2017
DOI: 10.1037/cdp0000118
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, discrimination, and depression among unauthorized Latinos/as in the United States.

Abstract: Results may indicate ethnic identity as a risk factor for this group through experiences of discrimination. Theoretical and practical implications are discussed in terms of advancing theory and from a multicultural counseling perspective, respectively. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 70 publications
6
53
2
Order By: Relevance
“…Research has also suggested that undocumented Latinos are frequent targets of prejudice and may experience high levels of discrimination in U.S. society (Cobb et al, 2016(Cobb et al, , 2017. As noted by Berry et al (2006), perceived discrimination is one of the most debilitating stressors that immigrants can face.…”
Section: Conceptualizing Acculturation: Berry's Bidimensional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has also suggested that undocumented Latinos are frequent targets of prejudice and may experience high levels of discrimination in U.S. society (Cobb et al, 2016(Cobb et al, , 2017. As noted by Berry et al (2006), perceived discrimination is one of the most debilitating stressors that immigrants can face.…”
Section: Conceptualizing Acculturation: Berry's Bidimensional Modelmentioning
confidence: 99%
“…Within the psychological literature, research on the acculturation experiences of undocumented Latino immigrants in the U.S. is just beginning. For example, Cobb, Xie, Meca, and Schwartz (2016) found that acculturation was positively associated with everyday discrimination and depressive symptoms among a community sample of undocumented Latinos. In another recent study, undocumented Latinos reported issues surrounding restricted social mobility and unfair treatment in society (Cobb, Meca, Xie, Schwartz, & Moise, 2017).…”
mentioning
confidence: 99%
“…Unfortunately, minimal research has examined U.S. national identity with Latinas/os. As an exception, both ethnic identity and national identity were significantly correlated with increased everyday discrimination among undocumented Latina/o adults (Cobb, Xie, Meca, & Schwartz, 2017). A longitudinal study with Latina/o college students found that U.S. national identity moderated the relationship between ethnic discrimination and change in ethnic identity such that high national identity was associated with increased commitment to the ethnic group (Fuller-Rowell et al, 2013).…”
Section: Cultural Identitymentioning
confidence: 97%
“…Further, the depressive symptoms and anxiety Rosa experienced are common for students who are undocumented (Suárez-Orozco, 2017). Tapping into Rosa’s resistance capital allows her to access a connection to her cultural identity that may serve as an important coping resource (Cobb et al, 2016); however, it is likely that she will continue to need counseling support as she deals with ongoing stress and anxiety. Critical to this endeavor is cultivating a space where immigrant-origin students feel comfortable sharing and disclosing information that is highly vulnerable and could put them at risk (Talleyrand & Vojtech, 2019).…”
Section: Ccw Case Studiesmentioning
confidence: 99%